Reestruturação, expansão e democratização do ensino superior público federal (1995-2010) : da reforma do estado ao novo desenvolvimentismo - Silva, Ivan Henrique de Mattos e (Universidade Federal de São Carlos, 2013)
This work has as goal a comparative analysis of the Higher Education policies (with the focus at the federal universities) in Brazil between 1995 (year of the creation of the Conselho Nacional de Educação, and beginning of the first term of President Fernando Henrique Cardoso) and 2010 (end of the second term of President Lula). The guiding hypothesis is that the creation of the CNE, in 1995, represents a repositioning of the education issue in Brazil and marks the beginning of a new phase of public policies related to the public Higher Education (specially the federal universities network), that can be divided into two moments that, even though having certain similarities, carry deep differences between each other: 1995-2002 (FHC’s administration) and 2003-2010 (Lula’s administration), being the first one identified with a restructuring of the federal universities network and the pursuit of efficiency and rationalization of the public funds already invested; while the second one approaches to the new developmentalism debate, promoting an expansion of the federal universities network, based on the pursuit of the democratization of access.
Keywords: Ensino superior; Novo desenvolvimentismo; Universidades federais; Higher education; New developmentalism; Federal universities; CIENCIAS HUMANAS::CIENCIA POLITICA